2017
DOI: 10.18203/2394-6040.ijcmph20173316
|View full text |Cite
|
Sign up to set email alerts
|

Oral health knowledge, attitude and practices among male Qassim university students

Abstract: Background: Good oral health not only promotes an individual to look and feel good, it also helps in preserving oral functions. Oral health is considered an integral part of an individual's overall health. The study was carried out to assess oral health knowledge and practices among male students of Qassim University.Methods: This study included five hundred and eight Students from (4) male colleges in Qassim University enrolled in that academic year were invited to participate in this survey using a self-admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 12 publications
1
20
2
Order By: Relevance
“…Oral hygiene is the process of protecting the oral cavity and keeping it healthy and clean by various modalities like brushing and flossing in order to prevent tooth decay and gum diseases [2]. It is the method of keeping oral cavity free from pathological conditions that affect mouth like gum diseases, cavities, mouth sores and ulcers [3].…”
Section: Introductionmentioning
confidence: 99%
“…Oral hygiene is the process of protecting the oral cavity and keeping it healthy and clean by various modalities like brushing and flossing in order to prevent tooth decay and gum diseases [2]. It is the method of keeping oral cavity free from pathological conditions that affect mouth like gum diseases, cavities, mouth sores and ulcers [3].…”
Section: Introductionmentioning
confidence: 99%
“…This research has shown that personal care for oral health maintenance among students of dental medicine is low at the beginning of health education intervention, and that further educational efforts are needed to achieve an overall improvement of oral health, habits, attitudes and behaviour of students 8,13 .…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, their knowledge, behaviour and attitudes should change positively over the years of study. Because professional (dental) students specialize in preventive information and health promotion, it is important that their own oral health knowledge, attitude, and practice are adequate 7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral hygiene is the process of protecting the oral cavity and keeping it healthy and clean by various modalities like brushing and ossing in order to prevent tooth decay and gum diseases [2]. It is the method of keeping oral cavity free from pathological conditions that affect mouth like gum diseases, cavities, mouth sores and ulcers [3].…”
Section: Introductionmentioning
confidence: 99%